Indices of free radical activity in the cerebrospinal fluid in motor neuron disease. Issue 7 (July 1987) - Mitchell, J D; Jackson, M J; Pentland, B
Abstract : Indices of free-radical activity and lipid peroxidation were studied in cerebrospinal fluid samples obtained from 11 patients with motor neuron disease and 11 reference subjects. No differences were found between the two groups. The significance of this finding is discussed in relation to current views of the possible pathogenesis of this disease.